New estimate of the elasticity of marginal utility of consumption for Europe: Implications for the social discount rate - Milan Ščasnýa; Matěj Opatrný (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We provide the first estimate of the elasticity of marginal utility of consumption, μ, for Europe and for thirty individual European countries, using the income-tax individual-level data. Specifically, we rely on the absolute equal-sacrifice approach and CRRA utility function to elicit the revealed preferences of income tax payers on their acceptance of the tax schedule. Our central estimate of μ equals to 1.42. With few exceptional cases, μ's for European countries exceed unity, ranging between 1.2 and 1.90. We further discuss the implications of our estimate of μ for the social discount rate and Social Cost of Carbon. We conclude that the social discount rate might be slightly higher than traditionally assumed, implying lower magnitude of Social Cost of Carbon, at least for Europe.
Keywords: D60; D61; H24; R13; 330; elasticity of marginal utility of consumption; equal-sacrifice approach; income tax schedules; marginal tax rate; social discount rate